2016
DOI: 10.3791/54815
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Soil Resampling to Monitor Changes in the Chemical Concentrations of Forest Soils

Abstract: Recent soils research has shown that important chemical soil characteristics can change in less than a decade, often the result of broad environmental changes. Repeated sampling to monitor these changes in forest soils is a relatively new practice that is not well documented in the literature and has only recently been broadly embraced by the scientific community. The objective of this protocol is therefore to synthesize the latest information on methods of soil resampling in a format that can be used to desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Sampling was repeated using the same methods at the same locations in North Buck in 2009–2010 and South Buck in 2014. The soil resampling procedures used in this study are further detailed in Lawrence, Fernandez, Hazlett, Bailey et al (). All soil samples were analyzed in the USGS Troy Laboratory following U.S. Environmental Protection Agency (USEPA) methods (Blume et al, ) and Thomas () as described in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…Sampling was repeated using the same methods at the same locations in North Buck in 2009–2010 and South Buck in 2014. The soil resampling procedures used in this study are further detailed in Lawrence, Fernandez, Hazlett, Bailey et al (). All soil samples were analyzed in the USGS Troy Laboratory following U.S. Environmental Protection Agency (USEPA) methods (Blume et al, ) and Thomas () as described in the supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…The soil samples were collected from thirteen trail pits of size 1 m 2 area at a depth of 2m as suggested by the pioneer researcher (Subramani et al, 2014) and tested for its physical characteristics to identify the soil erodibility rate. The testing was done on air-dried samples in a short period of time for a relative consistent analysis on both the physical and chemical characteristics as suggested by the pioneer researcher (Lawrence et al, 2016;Subash et al, 2017). For hydrometer analysis, the control solution was prepared such that 125 mL solution of 40 gL -1 sodium hexametaphosphate solution and 875 mL of water.…”
Section: Methodsmentioning
confidence: 99%
“…A threshold of 20% total C was used to confirm field identification of Oa and A horizons. Past studies have shown that small sampling errors at the interface of organic–mineral horizons can lead to large errors in chemical results (Yanai et al, 2005; Lawrence et al, 2016). To account for this possibility, concentration data for Oa and A horizons are presented in units of charge per mass of soil, and also in units of charge per mass of soil C to normalize for variations in C concentration (Warby et al, 2009).…”
Section: Methodsmentioning
confidence: 99%